Posledice pozebe v gozdu - Sinjur, Iztok (Gozdarski vestnik, 2017)
Frost causes damage both with fruit trees as with forest trees and shrubs. Regardless of this we seldom link it with damage in forests, since the consequences are seldom recognized as damage there, due to lesser dependence on yearly yields and spatial limitation. For the second year in a row, in April 2017 early phenological phases were followed by the cold air intrusion, due to which numerous trees and shrub species in many regions of Slovenia suffered frost damage. Since also some honey and park plant species were affected, the occurrence got major attention in public.
Keywords: frost; pozeba; pomlad; spring; forest; gozdovi; meteorologija; meteorology; Slovenia; Slovenija